Faktor-faktor yang berhubungan dengan kunjungan awal kehamilan (K1) - Mailisna Mailisna; Nurlaili Ramli; Evi Zahara; Isnaini Putri; Nizan Mauyah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Early pregnancy visit (K1) is the first contact of pregnant women with health workers, which is important for early detection of pregnancy complications. Data shows that K1 coverage at Sukamakmur Public Health Center is only 76%, meaning that 24% of pregnant women do not make K1 visits. Various factors influence the low number of K1 visits, such as knowledge, husband’s support, and culture. Purpose: To determine the factors related to early pregnancy visits (K1). Method: This study used a cross-sectional design with a quantitative analytical descriptive approach. The study population was 94 pregnant women in the second and third trimesters in the working area of ​​Sukamakmur Public Health Center, Aceh Besar. The sample was calculated using the Slovin formula with a 5% error tolerance limit, obtaining 85 respondents selected by purposive sampling. Primary data were collected using a questionnaire on knowledge (11 questions), husband’s support (20 likert scale questions), culture (10 questions), and secondary data through examination of the KIA book. Data analysis used univariate and bivariate analysis with the chi-square test at a significance level of p <0.05. Results: The results of the bivariate analysis showed a significant relationship between maternal knowledge and K1 visits (p = 0.009), husband’s support with K1 visits (p = 0.014), and culture (p = 0.032) with K1 visits. Conclusion: Maternal knowledge, husband’s support, and cultural factors were proven to be significantly related to early pregnancy visits (K1) in the Sukamakmur Health Center work area. Suggestion: It is necessary to improve reproductive health education programs, empower husbands in supporting ANC, and use a sensitive cultural approach to increase the scope of K1 visits